Computer Highlights Society Magazines. (Computer (00189162), 2009)
The article describes topics covered by articles from Institute of Electrical and Electronics Engineers (IEEE) publications published in 2009. The article "Cloud Computing: Does Nirvana Hide Behind the Nebula?" in the March/April 2009 issue of "Software" magazine considers the concept of software as a service which serves as the basis for cloud computing. The article "Parallel Programming With Skeletons," by Joel Falcou in the May/June 2009 issue of "Computing in Science & Engineering" discusses parallel programming in software development. The article "Cloud Computing: IT as a Service" in the March/April 2009 issue of "IT Professional" is also described, which discusses the presentations of large information technology companies at the 2008 IEEE International Conference on Web Services.